The Economic and Social Cost of IMF Conditionalities: A Case Study of Pakistan - Arafat, Dr. Yasir; Dr. Farahnaz Turi; Azra Amir, (Dialogue Social Science Review (DSSR), 2025)
The IMF's structural adjustment programs and other financial assistance have significantly impacted, for better or for worse, the economic policies of most, if not all, developing nations, including Pakistan. This study explores the relationship by considering the Ordinary people of Pakistan and the inflation, unemployment, poverty, GDP growth and right where it hurts the most government expenditure on public services. This study relies on secondary sources including data contained in documents and databases made available by governments or international organizations and seeks to establish the relationship between IMF policy interventions and selected variables through descriptive analyses and regression modeling methods. The results indicate that IMF programs indeed managed to stabilize the exchange rates and to reduce the fiscal deficits, however, they also induced lowered economic growth rate because of contractionary policies within the country. There was a sharp increase in the inflation rate during the programme years. At the same time, the increase in poverty as well as the increase in the unemployment rate fueled social vulnerabilities. Under austerity measures, public expenditure on priority areas such as health and education were reduced, worsening the population’s access to the services deemed as basic. This study contributes to a broader discussion of the effectiveness of IMF interventions and highlights the trade-off between macroeconomic stability and social well-being. This analysis highlights the need for a more effective policy approach to address structural challenges without imposing a burden on vulnerable groups in society.